Internalization of Islamic Ecotheological Values in Religious Counseling: A Case Study of Religious Counseling from the Maqāsid Syarī’ah Perspective - Muhammad Aniq; Ahmad Fauzan (Kopertais Wilayah X Jawa Tengah, 2026)
This study examines the internalization of Islamic ecotheological values in religious counseling practices in Demak Regency from the perspective of maqasid al-shariah. The research is motivated by the coastal environmental crisis in Demak, marked by shoreline abrasion and tidal flooding, which reflects both ecological degradation and a decline in spiritual awareness. Religious counseling is therefore viewed as a strategic instrument for fostering ecological consciousness. Using a qualitative case study approach, data were collected through in-depth interviews with 15 Islamic religious counselors, participant observation of 10 counseling activities, and content analysis of 15 Friday sermon manuscripts 2025. The data were thematically analyzed with source and methodological triangulation, employing maqasid al-shariah as the analytical framework. The findings indicate that ecotheological internalization occurs at three levels: cognitive, affective, and conative. Counselors contextualize Qur’anic concepts such as khalīfah fī al-arḍ and the prohibition of fasād fī al-arḍ within coastal realities, deliver them through empathetic da‘wah, and encourage collective actions such as mangrove planting and eco-mosque initiatives. However, these efforts remain fragmented due to limited training and weak institutional support. This study affirms environmental preservation (ḥifẓ al-bīah) as a fundamental objective of Islamic law and highlights the need to institutionalize ecotheological da‘wah within religious counseling systems.